The optimal structural analysis of cobalt-chromium alloy (L-605) coronary stents. Issue 14 (10th November 2021) - Wang, Huajie; Wang, Xianying; Qian, Hongliang; Lou, Deda; Song, Mingming; Zhao, Xiaoqian
Abstract: A coronary stent is a conventional medical device used in percutaneous coronary intervention (PCI), and its mechanical properties have become one of the critical factors to determine the effect of surgical treatment. Based on the existing cobalt-chromium (CO-Cr) alloy L605 coronary stent, this paper established an integrated finite element model of the stent-balloon-compression shell to simulate the stent bundle expansion test and crush resistance test with parallel plates. We verified the accuracy of the analytical model by comparing the simulation results with experimental results. The effects of different parameters on the axial retraction performance, the expansion uniformity, and the flexibility of the stent are analyzed by using the support body dimension and connector form as parameters. The results demonstrate that increasing the number and length of the circumferential support can improve the axial retraction performance, expansion uniformity, and the form of the connector has a significant influence on the flexibility of the stent. Finally, the optimized CO-Cr alloy stent with improved comprehensive indicators is described.